In the middle of the west - Gilroy, Steve (Oberon modern plays., 2018)
'That photo; that wasn't who Baylee was. She wasn't 'the baby in the fireman's arms.' She was my child.' In Oklahoma City on the morning of April 19th 1995, Timothy McVeigh detonated a truck bomb outside the Alfred P Murrah Federal building, killing one hundred and sixty-eight people. Through interviews In the Middle of the West gathers revealing and surprising first-hand accounts from those most intimately involved. Tragic, compelling and funny, the play (for up to over twenty performers), weaves together the dramatic and powerful stories of people whose lives were forever changed by what remains America's most destructive domestic terror attack. In the Middle of the West is also about Oklahoma, a frontier state whose people are characterized by their independence and determination. What is the lasting legacy for those caught up in this tragic event' How does its impact still resonate for Oklahoma City - a city in the middle of Mid-America' 'They're self-reliant and they feel like the government is getting too big' At some point they may say; 'We have to defend ourselves... from our own government. .'